Accuracy Test of Supermarket's Mushola Qibla Direction In Cirebon City - Samsudin Samsudin; Kusdiyana Kusdiyana; Rizal Ramadhan (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
This study aims to answer the questions that become the formulation of the problem “How is the method of measuring the Qibla direction of the supermarket prayer room in Cirebon City” and “How to analyze the accuracy of the supermarket prayer room Qibla direction in Cirebon City.” This study uses qualitative research; the data collected uses observation, interviews, documentation, and literature study. They were then analyzed by the descriptive analysis method in narration. The results of this study: that the Qibla direction of the supermarket in Cirebon City has all measured the Qibla direction. The method of measuring the Qibla direction was carried out by the musala supermarket, where the author’s research uses the Qibla compass and the Qibla direction application on the smartphone. Of course, using the Qibla direction application on a smartphone is an inaccurate method. This method’s method is partly an error in determining the Qibla direction. Due to his ignorance of astronomy in measuring the Qibla direction and ignorance of the magnitude of the Qibla direction angle in the Cirebon City area, resulting in the Qibla direction of the supermarket in the Cirebon City area experiencing a wrong Qibla direction.